2019
DOI: 10.3390/su11041195
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Factors Behind the Success and Sustainability of China’s Creative Research Group: An Extension of the Teamwork Quality Model

Abstract: The Creative Research Group (CRG) is the special high-level scientific and innovation team funded by the National Natural Science Foundation of China to promote basic research at the frontiers of science. In general, there are problems of “structure anomie” and “cooperation inefficiency” in the operations and teamwork dynamics within the nationwide CRG project. By extending and developing the two-stage teamwork quality model, this study aims to depict and analyze the impact factors behind the success and susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(176 reference statements)
0
12
0
Order By: Relevance
“…This study results showed similar relations to previous instances, namely that team synergy, innovation, and teamwork quality have positive relationships with team performance. The cohesion and synergy of team colleagues [36], teamwork quality [38], and innovative behavior [40] have positive relations with and lead to higher teamwork performance. This was an expected result, since team synergy brings greater cohesion and better cooperation between team members, which can lead to joint efforts to reach the proposed goals and achieve better results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study results showed similar relations to previous instances, namely that team synergy, innovation, and teamwork quality have positive relationships with team performance. The cohesion and synergy of team colleagues [36], teamwork quality [38], and innovative behavior [40] have positive relations with and lead to higher teamwork performance. This was an expected result, since team synergy brings greater cohesion and better cooperation between team members, which can lead to joint efforts to reach the proposed goals and achieve better results.…”
Section: Discussionmentioning
confidence: 99%
“…This was an expected result, since team synergy brings greater cohesion and better cooperation between team members, which can lead to joint efforts to reach the proposed goals and achieve better results. The innovation and quality of teams in terms of their processes and achievements, are seen as the leading factors for the competitiveness and sustainability of teams and their results [7,36,38]. Therefore, these three factors should be more carefully planned, monitored, controlled, and enhanced by team leaders and managers in order to keep teams effective and provide better results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoegl & Gemunden [13] constructed an operationalization of TWQ using 38 response items, with different number of items per facet: Communication (10), Coordination (4), Balance of Member Contribution (3), Mutual Support (7), Effort (4), and Cohesion (10). The factorial structure of the TWQ construct was tested using principal component analysis.…”
Section: Cohesionmentioning
confidence: 99%
“…Further, at least six other studies applied and extended TWQ in other context such as MBA student teams in USA [9], management teams in Indonesia [2], new product development in Germany [19] and Turkey [8], research teams in China [10], and electronics company in South Korea [3]. As these studies are no related to software development, they will not be discussed in this article.…”
Section: Introductionmentioning
confidence: 99%